Two Case Reports of Biliary Tract Injuries during Laparoscopic Cholecystectomy. (14th February 2011) - Romano, O.; Romano, C.; Cerbone, D.; Sperlongano, P.; Caserta, L.; Frega, N.; Cimmino, G.; D'Agostino, A.; Addeo, R.
Abstract : Background and Study Aims . Biliary tract injuries (BTI) represent the most serious and potentially life-threatening complication of cholecystectomy occurring also during laparoscopic approaches. Patients and Methods . We describe and discuss two different cases of BTI occurring during laparoscopic cholecystectomy (LC). Results . Two patients developed BTI during LC and one evidenced the complication during the LC itself and was treated during the same LC in real time. The other patient evidenced BTI only after the primary intervention and was successfully reoperated in laparotomy after 10 days from the LC. Conclusions . The factors that predispose to the occurrence of BTI during cholecystectomy and the cautions to be used to prevent BTI are discussed.